Al-Ṣarf al-Muyassar for Arabic Morphology Learning: Effects on Speaking and Reading Skills - M. Adlika; Menik Mahmudah (Lughawiyyat: Jurnal Pendidikan Bahasa dan Sastra Arab, 2023)
Arabic morphology is often taught through rule memorization and conjugational paradigms, although its contribution to speaking and reading requires further empirical examination. This study investigated the implementation and effectiveness of Al-Ṣarf al-Muyassar: Taqrīb Lāmiyyat al-Afʿāl in improving students’ Arabic speaking and reading skills. A quantitative quasi-experimental design with a pretest–posttest control group was employed. The participants were 40 second-year secondary students at Darullughah Wadda’wah Islamic Boarding School, Bangil, Indonesia, divided into an experimental group and a control group of 20 students each. The experimental group received morphology instruction through simplified rules, root-and-pattern analysis, tables, guided exercises, reading activities, and oral sentence production, while the control group received conventional morphology instruction. Data were collected through speaking and reading tests, classroom observation, and teacher interviews. The experimental group’s mean score increased from 68.5 to 85.8, whereas the control group improved from 68.2 to 74.6. The posttest difference was statistically significant (p = .001), indicating that Al-Ṣarf al-Muyassar-based instruction produced stronger combined speaking and reading outcomes. The findings suggest that Arabic morphology becomes more effective when structural knowledge is connected with contextualized reading and oral production. This study contributes evidence that simplified and application-oriented morphology instruction can transform ṣarf from a memorized body of rules into a functional foundation for receptive and productive Arabic skills in an Indonesian Islamic boarding-school context.